Study the Effect of Inhalation of Peppermint Oil on Depression and Anxiety in Patients with Myocardial Infarction who are Hospitalized in Intensive Care Units of Sirjan - AA Vaezi; S Parizi; AR Vahidi; H Tavangar (Institue of Medicinal Plants, ACECR, 2017)
Background: A psychological reaction such as depression and anxiety is a complication of a heart attack. The aromatherapy is one of the processes in Complementary medicine to maintain mental health of diseases. Objective: This study aimed to investigate the effect of inhalation of essential oil on depression and anxiety in patients with acute myocardial infarction. Methods: This Clinical trial study was conducted in 70 heart attack patients by purposive sampling method and randomly divided in two groups (Intervention and control) who were hospitalized in intensive care units of Sirjan in year 2015. Data were collected by self-report DASS-21 questionnaires. In intervention group 0.2 ml of peppermint oil mixed with 2 ml of Normal saline and in control group 2 ml of normal Saline was poured on a gas and attached with clamp to the collar of patients for 20 minutes and inhaled it for 5 days. Before and after the intervention patients completed DASS-21 questionnaire. After collecting the data Inter to SPSS 21 software and using chi-square tests, t-test were analyzed. Results: The age of control and intervention groups was 57.62±11.48, 54.94±10.53 respectively. After aromatherapy in the intervention group in comparative of before intervention and control group, the level of anxiety and depression in patients significantly showed decreased (P=0.001). Conclusion: According to the results of this study, treatment with peppermint oil can reduce depression and anxiety in patients with myocardial infarction, so its use is recommended in clinical situations.